Identification and diagnostic performance of a small RNA within the PCA3 and BMCC1 gene locus that potentially targets mRNA - Drayton, Ross M.; Rehman, Ishtiaq; Clarke, Raymond; Zhao, Zhongming; Pang, Karl; Miah, Saiful; Stoehr, Robert; Hartmann, Arndt; Blizard, Sheila; Lavin, Martin; Bryant, Helen E.; Martens-Uzunova, Elena S.; et al. (Cancer Epidemiology Biomarkers & Prevention, 2015)
PCA3 is a long noncoding RNA (lncRNA) with unknown function, upregulated in prostate cancer. LncRNAs may be processed into smaller active species. We hypothesized this for PCA3.We computed feasible RNA hairpins within the BMCC1 gene (encompassing PCA3) and searched a prostate transcriptome for these. We measured expression using qRT-PCR in three cohorts of prostate cancer tissues (n = 60), exfoliated urinary cells (n = 484 with cancer and n = 166 controls), and in cell lines (n = 22). We used in silico predictions and RNA knockup to identify potential mRNA targets of short transcribed RNAs.We predicted 13 hairpins, of which PCA3-shRNA2 was most abundant within the prostate transcriptome. PCA3-shRNA2 is located within intron 1 of PCA3 and appears regulated by androgens. Expression of PCA3-shRNA2 was upregulated in malignant prostatic tissues, exfoliated urinary cells from men with prostate cancer (13-273 fold change; t test P < 0.003), and closely correlated to PCA3 expression (r = 0.84-0.93; P < 0.001). Urinary PCA3-shRNA2 (C-index, 0.75-0.81) and PCA3 (C-index, 0.78) could predict the presence of cancer in most men. PCA3-shRNA2 knockup altered the expression of predicted target mRNAs, including COPS2, SOX11, WDR48, TEAD1, and Noggin. PCA3-shRNA2 expression was negatively correlated with COPS2 in patient samples (r = -0.32; P < 0.001).We identified a short RNA within PCA3, whose expression is correlated to PCA3, which may target mRNAs implicated in prostate biology.This short RNA is stable ex vivo, suggesting a role as a robust biomarker. We identify cytoplasmic enrichment of this RNA and potential targeting of mRNAs implicated in prostate carcinogenesis.
EVALuna2:6667